Quality of life in individuals with spinocerebellar ataxia type 10: a preliminary study - Santos, Laudiane Reis; Teive, Hélio Afonso Ghizoni; Lopes, Francisco Diego Negrão, Neto; Macedo, Ana Carolina Brandt de; Mello, Neliana Maria de; Zonta, Marise Bueno (Arquivos de Neuro-Psiquiatria, 2018)
Spinocerebellar ataxia type 10 (SCA10) is characterized by gait ataxia, dysarthria, nystagmus, epilepsy, reduced cognitive ability and depression, which lead to functional loss and behavioral changes. These signs gradually evolve and may interfere with the physical, emotional, and social aspects of quality of life (QoL).Objective: To assess the self-perception of quality of life and its association with disease duration, severity of ataxia, balance and functional independence.Methods: This study focused on the disease duration, ataxia severity (SARA), balance (Berg Balance Scale), functionality (FIM, Lawton IADL) and QoL (SF-36 v.2) of 15 individuals with SCA10.Results: The population sample consisted of eight females and seven males, with a mean age of 43.8 (± 8.2) years, mean age of symptom onset of 33.1 (± 8.9) years and mean disease duration of 9.8 (± 11.2) years. The mean Berg Balance Scale score was 47.2 (± 12), mean SARA score (n = 14) 11.5 (± 7.3), mean Lawton IADL score 20.4 (± 1.8) and mean FIM score 120.3 (± 5.4). Individuals with SCA10 had a greater impairment of QoL in the “role-physical” domain (p = 0.04). The longer the disease duration (p = 0.02), risk of falling (p = 0.04), severity of ataxia (p = 0.00) and functional dependence in activities of daily living (p = 0.03) and instrumental activities of daily living (p = 0.00), the worse the QoL was in the “physical functioning” domain, with a decrease of 1.62 points for each year of disease duration.Conclusion: In this sample, the greatest impairment of QoL in individuals with SCA10 was observed in “physical functioning” and “physical role”.
Keywords: spinocerebellar ataxias; quality of life; surveys and questionnaires